IMPLEMENTATION OF ARTIFICIAL NEURAL NETWORK FOR CLUSTTERING OF STUDENTS INTERESTING IN COMPUTING FIELDS - WIJI LESTARI; SRI SUMARLINDA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The computing field interested is important for students of the Faculty of Computer Science. Student interest also relates to research for the thesis required for graduation. At the Faculty of Computer Science, University of Duta Bangsa Surakarta, there are several research topics that are of interest to students including: Information Systems, Decision Support Systems, Multimedia, Expert Systems and Intelligent Information Systems. Clustering is a method for grouping a number of data into several clusters or groups. Data that have closeness will be grouped into one cluster. Competitive Network is part of Artificial Neural Networks with unsupervised learning. This algorithm can be used for clustering. This study aims to produce a clustering system for mapping students interests on research topics at the Faculty of Computer Science, Duta Bangsa University Surakarta with a competitive network artificial neural network. The input data used were the results of the student's focus questionnaire on research topics which would be grouped into 5 clusters. The clustering process uses the Competitive Network algorithm with clustering parameters of the number of clusters 5, 1000 and Kohonen parameter of 0.01